Effect of nitrogen sources on fermentation process and formation of hydrogen sulfide and ethyl carbamate by wine yeast - Nowak, Agnieszka; Koch-Wilk, Magdalena; Pogorzelski, Eugeniusz; Czyżowska, Agata (Wydawnictwo Politechniki Łódzkiej, 2013)
The addition of nitrogen compounds during winemaking is required for the fermentation process to be conducted properly. These compounds are known to be essential to the vinification process, not only because they influence yeast growth but also because they affect the formation of main and by-products. The effect of nitrogen source on in vitro and in situ formation of hydrogen sulfide and ethyl carbamate was studied. Research material comprised two strains of wine yeast: Saccharomyces cerevisiae. In vitro model was carried out in a synthetic defined medium. In situ fermentations were carried out in musts prepared from apple concentration. The process of hydrogen sulfide formation was intensified in nitrogen deficiency. The presence of amino acids in a model substrate resulted in significant changes in the efficiency of formation of both compounds. Yeasts produced more H2S in the presence of Cys, Phe, Gly, Glu, Ile, Thr, Pro, Leu, Trp, Val and less in the presence Ala, Arg, Asp, His, Ser, Met. The formation of ethyl carbamate was limited by the amino acids, except Arg, Asp and Lys, which during fermentation with Syrena yeasts caused an increase in the efficiency of formation of this compound. The Fermivit V preparation stimulated yeasts to form H2S. In the presence of this preparation the Syrena yeasts formed more ethyl carbamate while Hefix yeasts formed about 3-fold less of this compound then in the presence diamonium phosphate.
Keywords: hydrogen sulphide; ethyl carbamate; wines; yeasts; siarkowodór; karbaminian etylu; wina; drożdże